THE INFLUENCE OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND SALES PROMOTION TO REPURCHASE INTENTION OF E-WALLET USERS: CASE STUDY OF OVO IN SIDOARJO - Latifa Al Rosyidah Imas (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research is aimed to determine the influence of perceived usefulness, perceived ease of use, and sales promotion to repurchase intention of e-wallet users in Sidoarjo, specifically OVO users. The purpose of this research is to find whether perceived usefulness, perceived ease of use, and sales promotion have significant influence towards repurchase intention of OVO users in Sidoarjo. The research variables are independent variables which include Perceived Usefulness (X1), Perceived Ese of Use (X2), Sales Promotion (X3), and dependent variable which includes Repurchase Intention (Y). This research used a quantitative approach and is explanatory research which used a specific hypothesis. In data collection process, an online questionnaire was distributed with a 5-point Likert Scale. Respondents criteria of this research are those who use OVO and are domiciled in Sidoarjo. Samples taken were as many as 158 respondents of OVO users in Sidoarjo. The data of this research was analysed by Multiple Linear Regression, t-test as hypothesis testing, and IBM SPSS Statistics ver. 23.0 as an analysis tool. Keywords: Perceived Usefulness, Perceived Ease of Use, Sales Promotion, Repurchase Intention